(Dis)courtesy Bias: "Methodological Cognates, " Data Validity, and Ethics in Violence-Adjacent Research. (March 2022) - Parkinson, Sarah E.
In settings where war, forced migration, and humanitarian crisis have attracted international attention, research participants' prior experiences with journalists, advocacy groups, state security, and humanitarian organizations influence scholarly work. Building on long-term fieldwork in Iraq and Lebanon, this article argues that individuals' and communities' previous and ongoing interactions with these actors affect the content, quality, and validity of data gathered as well as shaping possibilities for ethical academic research. Drawing on observational and interview-based research with humanitarian service providers, journalists, and displaced persons, this article argues that the cross-sector use of "methodological cognates" such as surveys and structured interviews shapes data validity and reliability via four mechanisms: regurgitation, redirection, reluctant participation, and resistance. I contend that these features of the research process should centrally inform academics' research designs, project siting, case selection, and data analysis.